Bisulfite-free and base-resolution analysis of 5-methylcytidine and 5-hydroxymethylcytidine in RNA with peroxotungstate - Yuan, Fang (Royal Society of Chemistry, 2019)

(untitled) (Chem Commun (Camb))
5-Methylcytosine (5mC) and 5-hydroxymethylcytosine (5hmC), two of the best-studied DNA modifications, play crucial roles in normal development and disease in mammals. Although 5-methylcytidine (m(5)C) and 5-hydroxymethylcytidine (hm(5)C) have also been identified in RNA, their distribution and biological function in RNA remain largely unexplored, due to the lack of suitable sequencing methods. Here, we report a base-resolution sequencing method for hm(5)C in RNA. We applied the selective oxidation of hm(5)C to trihydroxylated-thymine ((th)T) mediated by peroxotungstate. (th)T was subsequently converted to T during cDNA synthesis using a thermostable group II intron reverse transcriptase (TGIRT). Base-resolution analysis of the hm(5)C sites in RNA was performed using Sanger sequencing. Furthermore, in combination with the TET enzyme oxidation of m(5)C to hm(5)C in RNA, we expand the use of peroxotungstate oxidation to detect m(5)C in RNA at base-resolution. By using this method, we confirmed three known m(5)C sites in human tRNA, demonstrating the applicability of our method in analyzing real RNA samples.